Seismic protection of an aqueduct by innovative techniques - Chrysostomou, Christis; Demetriou, Themos; Stassis, Andreas; Hamdaoui, Karim (My University, 2004)
The effectiveness of the use of Cu‐based shape memory alloy (SMA) prestressing devices on an ancient aqueduct is examined in this paper. The dynamic characteristics of the aqueduct were measured within the span of three years and computational models were developed that matched very closely its dynamic behaviour. Using this as a bench mark, SMA prestressing devices were applied on the structure and the effects on its dynamic characteristics were assessed. It was noted that the SMA prestressing devices have a significant effect on the dynamic response of the structure. This is attributed to the stiffening of the structure due to the increase in contact between the masonry units and hence the increase of its stiffness through the increase of the modulus of elasticity of the masonry matrix. It can be concluded that the SMA prestressing devices can provide an inconspicuous means of stiffening masonry structures and increase their resistance to earthquake loads.
Keywords: Shape memory effect; Computational Models; Seismic instruments; Earthquakes; Elastic moduli